PENGARUH SISTEM PERPAJAKAN YANG KONDUSIF TERHADAP DUNIA USAHA - SADHA SUARDIKHA, I MADE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 2 (2007), 2007)
There are two parties in taxation system which has different interests. Thefirst party is known as fiskus, in this case Direktorat Jenderal Pajak, and societyor tax payer as the second party. Direktorat Jenderal Pajak has tried to maximizethe tax income collected from the society based on their authority under thecurrent taxation law. In contrast, the tax payer has also tried to optimize theirobligation based on the humanity characteristic of human being or the economicprinciples of business entities. In order to modernize the taxation system, there isa problem occur between Direktorat Jenderal Pajak and society as tax payer. Theproblem is how the Direktorat Jenderal Pajak be able to encourage conduciveinfluence on business community as a current implication of their taxation system.The application of taxation system will positively affect the business community ifthe harmonization of relationship between both parties takes place. Therefore, theharmonization between tax payer and fiskus may be able to persuade conduciveenvironment on business community.
Keywords: taxation system, fiskus, tax payer, business community